Pemberdayaan Ekonomi Disabilitas Melalui Batik Ciprat - Hanik Fitriani (Amaluna: Jurnal Pengabdian Masyarakat, 2022)
One of the poor people in Simbatan Village, Nguntoronadi Magetan, is dominated by persons with disabilities who are considered marginal people, so empowerment assistance is needed, especially in the economic field so that people with disabilities are able to be independent. The research method in this research is qualitative research that relies on economic effectiveness in the community, in this case, disability in Simbatan Village, Nguntoronadi District, Magetan, with a field research approach. The data in this study are 25 disabilities who are members of the SW. Kontakroso as the object under study. The results in this study were that persons with disabilities who were considered not independent were given training and assistance in making splashed batik and sewing through the stages of briefing, batik training, sewing training, implementation, marketing training and finally monitoring and evaluation. The conclusion from this study is that the economic condition of disabled people in Simbatan Village belongs to the category of poor people, so empowerment assistance is needed as an effort to make people with disabilities independent and productive, not dependent on normal society. b). The empowerment strategy is carried out by providing training on sprinkling batik and sewing as well as providing assistance in the field of marketing with an online marketing strategy through social media that does not yet exist, so that products with disabilities can be recognized by local, national and international markets.